Analysis on Volatile Components in Mentha haplocalyx of Special Herbs in Qinghai Province - Su1, Xu; Liu3, Yu-Ping; Chen1, Ke-Long (Asian Journal of Chemistry, 2014)
The qualitative and quantitative analysis is performed on the volatile components in Mentha haplocalyx of special herbs in Qinghai Province by SPME-GC-MS. The relative percentage content of each component was calculated with peak area normalization method. There were 42 components separated from Mentha haplocalyx. The main constituents were ketones, alkenes, aromatic and ester compounds. The component of highest concentration was 2-methyl-5-(1-methylethenyl)cyclohexanone which reached 39.54 %.